Pengaruh Pelatihan, Penerapan Standar Operasional Prosedur (SOP), Sistem Penghargaan dan Lingkungan Kerja Fisik Terhadap Produktivitas Kapster/Barber (Studi pada J&K Barber Shop Medan) - Benny Tri Syahputra; Muhammad Arifin Nasution (Medan Resource Center, 2022)
This article discusses the effect of training, the application of SOPs on the productivity of barbers/capters at J&K Barber shop Medan, North Sumatra, Indonesia. The primary data obtained from the study were then analyzed using the Partial Least Square method with the help of Smart PLS Version 3.0 software. This research is an associative research type with a quantitative approach and by using purposive sampling with a sample of 30 respondents. The results of this study indicate that the independent variable training has a significant effect on the productivity of the barber/capster, then followed by the independent variable, the physical work environment, which has a significant effect on the productivity of the barber/capster. In addition, in this study, it was found that the independent variable of the reward system did not have a significant effect on the productivity of barbers/capters, the same thing also found that the independent variable of SOP implementation did not have a significant effect on the productivity of barbers/capters at J&K Barber shop Medan.